Collaborative and Reflective Learning Approaches in Biology Teacher Preparation: Emerging Insights and Future Directions - Marlina, Reni; Yuenyong, Chokchai; Hamdani, Hamdani; Pamungkas, Rahmania; Zb, Aminah (International Journal of Education and Teaching Zone, 2025)
This study aims to analyze research trends and characteristics related to collaborative reflective learning in educational contexts, particularly among pre-service biology teachers, and to recommend courses that align with this strategy. The method used in this study was a Systematic Literature Review (SLR). The researchers reviewed 33 scientific articles selected based on the criteria of being in English, published in reputable journals indexed by Scopus, and published between 2000 and 2025. The results revealed a significant increase in publications on this topic since 2018, with a peak in 2020 and 2024, which may have been influenced by the COVID-19 pandemic and the application of technology in online learning. The results also revealed that the concept of "collaborative" is often associated with professional identity, teaching and learning processes, and teacher competency development. Overall, research trends indicate that collaborative reflective learning is a strategic approach to professional development and pedagogical innovation. These strategies are crucial for preparing pre-service biology teachers who are adaptive and competent. This approach not only deepens understanding of biological concepts but also enhances critical thinking, problem-solving, and reflective skills. Through the implementation of this strategy, prospective teachers are expected to develop strong pedagogical competencies and be ready to face the challenges of 21st century education.